2016
DOI: 10.1016/j.ajodo.2016.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Surgical and orthodontic management of maxillary canine-lateral incisor transpositions

Abstract: Transposition of the maxillary canine and the lateral incisor is a complex dental anomaly to treat. The difficulty increases if the treatment aims to correct the transposition. These case reports describe 2 patients with transposition of the maxillary lateral incisor and canine. The first case involves bilateral incomplete transpositions, and the second is a complete transposition. The radiographic appearance of the canine was similar in the 2 patients. However, the treatments were distinct because of the 3-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 15 publications
0
5
0
2
Order By: Relevance
“…At the end of treatment, a slightly greater root resorption of the right first maxillary premolar was observed, perhaps due to greater forces applied on it to control root inclination and angulation (Figure 6). The short treatment time and the use of light forces may have contributed to the clinically acceptable resorption compared to similar cases in the literature (Lorente et al, 2016;Nishimura et al, 2012;Yan et al, 2012). The gingivae of the transposed teeth showed no signs of inflammation or recession.…”
Section: Discussionmentioning
confidence: 65%
“…At the end of treatment, a slightly greater root resorption of the right first maxillary premolar was observed, perhaps due to greater forces applied on it to control root inclination and angulation (Figure 6). The short treatment time and the use of light forces may have contributed to the clinically acceptable resorption compared to similar cases in the literature (Lorente et al, 2016;Nishimura et al, 2012;Yan et al, 2012). The gingivae of the transposed teeth showed no signs of inflammation or recession.…”
Section: Discussionmentioning
confidence: 65%
“…The less the canine has descended into its position, the wider the dentoalveolar process will be; this provides the opportunity to move the teeth within the bone and decreases the risk of negative effects. 23 In this case report, one of the main disadvantages was that the initial position of the canine crowns was not as high as desired to benefit the correction of the transposition. This was a challenge when designing the correct vector of traction, making the canine of the complete transposition move upward in order to avoid root contact during the displacement (Figure 4).…”
Section: Discussionmentioning
confidence: 91%
“…14 However, other authors reported cases in which transpositions have been corrected. 23,24 Canines are essential both for function, providing canine guidance for occlusion, as well as for esthetics, giving the patient correct dental and gingival symmetry. 21 In addition, from a facial esthetics point of view, the canine eminence provides support to the nasolabial fold, which will help the patient have better facial aging, and a greater sense of width in the smile is achieved.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, as the prevalence of the condition is relatively low, there is a lack of studies to aid determining not only the most effective treatment modality, but also the most convenient moment to begin. 24 …”
Section: Discussionmentioning
confidence: 99%